Strategi Guru Pendidikan Agama Islam Dalam Menyempurnakan Akhlakul Karimah Siswa - Muhammad Arsyad; Marwazi Marwazi; Musli Musli (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article reveals the strategy of Islamic Religious Education teachers in perfecting the morals of students at Junior High School 7, Muaro Jambi Regency, as well as the factors that support and inhibit this strategy. The issues raised in this article are how the morals of the students in the school are and what the Islamic Religious Education teacher's strategy is in perfecting the morals of the students. This article originates from a qualitative research that is descriptive-analytical using data derived from interviews, observation and documentation. The research findings show that the Islamic Religious Education teacher's strategy to perfect student morals is not optimal even though they have carried out habituation activities, set an example, educate students to be disciplined, reward and punishment. Even so, teachers still try to be able to overcome these things with ongoing planning and monitoring so that they can perfect the morals of the students. Artikel ini mengungkap strategi guru Pendidikan Agama Islam dalam menyempurnakan akhlak karimah siswa di Sekolah Menengah Pertama Negeri 7 Kabupaten Muaro Jambi serta faktor-faktor yang menjadi pendukung dan penghambat strategi tersebut. Permasalahan yang diangkat dalam artikel ini adalah bagaimana akhlak siswa di sekolah tersebut dan bagaimana strategi guru Pendidikan Agama Islam dalam menyempurnakan akhlak karimah siswa. Artikel ini berasal dari penelitian kualitatif yang bersifat deskriptif analitis dengan menggunakan data-data yang berasal dari wawancara, observasi maupun dokumentasi. Temuan penelitian menunjukkan bahwa strategi guru Pendidikan Agama Islam untuk menyempurnakan akhlak siswa belum optimal walaupun sudah melakukan kegiatan pembiasaan, memberikan teladan, mendidik siswa untuk disiplin, reward dan punishment. Meskipun demikian, guru tetap berupaya untuk dapat mengatasi hal-hal tersebut dengan perencanaan dan pemantauan berkelanjutan agar dapat menyempurnakan akhlak karimah siswa.